Acute Abdomen in Gynecology — Single University Centre Experiences - Dubravko Habek; Jadranka Ristić; Anis Cerovac (Clinical and Experimental Obstetrics & Gynecology)
Background: Acute abdomen (AA) is a synonym for a condition caused by an acute disease of an intra-abdominal organ that requires urgent surgical intervention. The gynecological-obstetrical etiopathogenesis of AA is based on pathological events on the genital organs due to hemorrhagic, inflammatory, and ischemic/obstructive genesis, and is a significant reason for admission to emergency gynecological departments, and emergency surgery. Methods: A retrospective clinical research was performed from 2005 to 2021, from the surgical protocol of the University Department for Gynecology and Obstetrics, Clinical Hospital “Sveti Duh” in Zagreb. In the examined sixteen-year period, 703 patients (4.06%) had surgery with a diagnosis of AA. Results: The largest number of surgeries due to AA was performed in the age group of 21–45 years (74.40%), i.e., in the reproductive age, followed by 106 patients aged 46–52 years (15.07%), then 46 (6.54%) patients in children and adolescent age up to 20 years of age, then from 53–60 years 23 (3.27%) patients, and in the elderly >60 years old, with 5 (0.71%) patients. The etiopathogenetic factors of AA were: the most common intra-abdominal hemorrhage in 68.14%, followed by inflammation and the most common complications of pelvic inflammatory disease in 25.60%, ischemic-obstructive causes in 2.56% and other causes in 3.7%. Out of the total number of surgeries, 450 (64.01%) were due to ectopic tubal pregnancy. Out of the total number of surgeries, 549 (78.09%) were performed (completed) by laparoscopy procedures, and by laparotomy and/or relaparotomy in 154 cases (21.90%). Regarding laparoscopy, 93.48% was performed in the age group up to 20 years, 83.56% in the age group of 21–45 years, and 62.26% was performed in the age group of 46–52 years. Regarding laparotomy, 69.57% was performed in patients aged 53–60 years, and 100% in the age group of patients >60 years. A pathological substrate was found for all operated patients, which they undergo for surgery, and we had no cases in which we did not prove a perioperative or pathohistological reason for AA. There were no patients’ deaths in the current study, which had to undergo for surgery for AA. Conclusions: We emphasize the urgent need for proper and continuous education of hospital teams, as well as extra-hospital emergency teams in recognizing AA symptoms of gynecological genesis based on history, clinical palpation examination, and ultrasound examination as a fundamental triad in the diagnosis of this life-threatening condition that requires only surgical treatment.